1990
DOI: 10.1108/eum0000000000873
|View full text |Cite
|
Sign up to set email alerts
|

Women′s Adaptation to Male‐dominated Occupations

Abstract: 2015),"The effect of workplace diversity management in a highly male-dominated culture", Career Development International, Vol. 20 Iss 3 pp. 259-272 http://dx. Access to this document was granted through an Emerald subscription provided by emerald-srm:226685 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…For men, however, working life experiences did not provide such a challenge since they are likely to have internalized such an achievement and instrumental orientation already before entering working life. Gomez‐Meija (1980) also argues that women when placed in a work setting with accentuated male norms may be more prone to internalize these norms over time than men are in the corresponding situation.…”
Section: Discussionmentioning
confidence: 99%
“…For men, however, working life experiences did not provide such a challenge since they are likely to have internalized such an achievement and instrumental orientation already before entering working life. Gomez‐Meija (1980) also argues that women when placed in a work setting with accentuated male norms may be more prone to internalize these norms over time than men are in the corresponding situation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this argument, Brief, Rose, and Aldag's (1977) analysis of survey data from a national sample of full-time employees in 1974 showed that once occupation was taken into account, the effects of gender on preferences for job characteristics were non-significant. Similarly, a study by Gomez-Mejia (1990) of employees in a single corporation indicated that the effects of occupational differences on work attitudes and preferences were much more pronounced than gender differences (see also Brief & Oliver, 1976;Lacy, Bokemeier, & Shepard, 1983;Saleh & Lalljee, 1969). Along the same lines, Bielby and Bielby (1989), using data from a 1977 national survey of workers, found that men and women engaged in similar work had an equal level of commitment to work.…”
Section: Prior Studies Of Gender Differences In Job Preferencesmentioning
confidence: 92%
“…Such analyses cannot reveal whether observed changes are limited to younger, more recent members of the labor force or reflect shifts that have affected all age groups over time (i.e., are due to cohort or period effects; see Ryder, 1965). Moreover, previous studies have shown that the work attitudes and values of younger workers are more apt to shift over time than are those of older workers (Finn, 1986;Gomez-Mejia, 1990;Posner & Powell, 1990;Spitze & Waite, 1980). Whether this is due to the fact that younger workers are more likely to experience significant changes in then work environments (because job and occupational shifts are more common at younger ages), or that older workers react less to changes in their work environment is not clear (Lorence, 1987;Lorence & Mortimer, 1985).…”
Section: Prior Studies Of Gender Differences In Job Preferencesmentioning
confidence: 99%
“…To believe that job seekers preference would be invariant across labor market conditions fails to reflect the realities faced by job seekers, questioning the ecological validity of previous research (Cable and Judge 1996;Saini et al 2014Saini et al , 2015Saini et al , 2018. For instance, previous streams of research on job attribute preferences of general population (e.g., Gallie et al 1998;Sutherland 2012), specific populations, such as African Americans (e.g., Murphy and Collins 2015), and graduating students (e.g., Sheppard 2018) as well as research based on gender ideology (e.g., Konrad et al 2005) and organizational socialization (e.g., Gomez-Mejia 1990) have ignored the influence of both return on investment, a key human capital metric, and labor market dynamics. In contrast, drawing on human capital theory, we surmised that expected rate of return, calculated as starting salary/educational fees would influence attributes job seekers prefer.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, other research has reported that although women rated job accommodations to family life and pleasant working conditions (e.g., flexible work hours, ease of work commute) higher than men, there were no significant gender differences in the importance of pay, intrinsic job qualities, or factors related to promotions and job perquisites (Heckert et al 2002). Based on these findings, some scholars (Brief and Aldag 1975;Brief and Oliver 1976;Gomez-Mejia 1990;Lacy et al 1983) have argued that socialization within the workplace is more crucial than the gender socialization that occurs outside the workplace. To be sure, whatever relationship exists between these variables is influenced by factors, such as family responsibilities, and life cycle stage among other factors (Konrad et al 2005).…”
Section: A Selected Review Of Job Attributes Literaturementioning
confidence: 99%